Anti-TNF therapy - Udalova, I; Monaco, C; Nanchahal, J; Feldmann, M (American Society for Microbiology, 2016)
Tumor necrosis factor (TNF) is one of the most important cytokines produced by macrophages. TNF is a very important component of host defense, released very rapidly after all types of injuries and stimuli. The kinetics of TNF release are short, and so it is perhaps not surprising that prolonged TNF production is associated with pathology. This was first elucidated in rheumatoid arthritis but extends to other chronic inflammatory diseases such as Crohn’s disease and psoriasis. In this chapter, the discovery of anti-TNF therapy is reviewed, with its benefit but also its limitations. The potential of anti-TNF therapy in other diseases, e.g., cardiovascular and fibrosis, is discussed, as is the opportunity to define ways of blocking TNF synthesis.